أقوال الامام الزهراوي في التفسير من خلال المحرر الوجيز لابن عطية الاندلسي في الربع الثاني من القران جمعا ودراسة - بوزق, أحمد (University of Eloued جامعة الوادي, 2020)
"ملخّص البحث هذا البحث بعنوان: ""أقوال الإمام الزّهراويّ في التّفسير من خلال المحرّر الوجيز لابن عطيّة الأندلسيّ في الرّبع الثّاني من القرآن الكريم -جَمعا ودراسة-""، وكان الإشكال الرّئيسي فيه يدور حول بيان منهجه في التّفسير, والقيمة العلميّة لأقواله؛ وقد حاولت الإجابة عن هذه الإشكاليّة، فخلصت إلى تقسيم البحث إلى مقدّمة, ومبحث تمهيديّ, وثلاث مباحث رئيسيّة, وخاتمة؛ تضمّنت المقدّمة بيانا لأهميّة الموضوع، وأهدافه، ومنهجي فيه؛ أمّا المبحث التّمهيديّ فقد اشتمل على الجانب النّظري له، فتطرّقت إلى المحاور الأساسية والمتعلّقة بترجمة الإمام الزّهراويّ، والتعريف بتفسيره، والتّعريف بابن عطيّة وبتفسيره؛ ثمّ انتقلت إلى الجانب التّطبيقي، وهي المباحث الثّلاثة الرئيسيّة في البحث, تحدّثت فيها عن أقواله في التّفسير (بالمأثور, وبالرّأي, وفي علوم القرآن), كلّ نوع في مبحث؛ وختمت بحثي بذكر جملة من النّتائج, أهمّها: أنّ تفسير الإمام الزّهراويّ من المصنّفات الجامعة بين الرّواية والدّراية, ما جعل المفسّرين من بعده يهتمّون به."Abstract This research is entitled: “The sayings of Imam al-Zahrawi on exegesis through the brief editor of Ibn Atiya al-Andalusi in the second quarter of the Holy Qur’an - collection and study -”. I tried to answer this problem, and concluded by dividing the research into an introduction, an introductory topic, three main discussions, and a conclusion. The introduction included a statement of the importance of the topic, its objectives, and its methodology. As for the introductory topic, it included the theoretical side of it, and it dealt with the basic themes related to the translation of Imam Al-Zahrawi, the definition of his interpretation, and the definition and interpretation of Ibn Atiyah. Then I moved to the practical aspect, which are the three main subjects in the research, in which I talked about his sayings on interpretation (by tradition, opinion, and science of the Qur’an), each type in a topic. I concluded my research by mentioning a number of results, the most important of which are: The interpretation of Imam Al-Zahrawi is one of the collections that combines the narration and knowledge, which made the commentators after him pay attention to it."
مذكرة ماستر تخصص تفسير وعلوم قرآن
Keywords: الزهراوي، تفسير، ابن عطية; al-Zahrawi، exegesis، Ibn Atiya